2018
DOI: 10.4093/dmj.2017.0106
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and the Risk of Diabetes and Dysglycemia in Korean General Adult Population

Abstract: BackgroundInsulin resistance is a major pathogenic hallmark of impaired glucose metabolism. We assessed the accuracy of insulin resistance and cut-off values using homeostasis model assessment of insulin resistance (HOMA-IR) to classify type 2 diabetes mellitus (T2DM) and dysglycemia according to age and sex.MethodsIn this cross-sectional study, we analyzed 4,291 anti-diabetic drug-naïve adults (≥20 years) from the 6th Korea National Health and Nutrition Examination Survey in 2015. Metabolic syndrome (MetS) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 35 publications
(40 reference statements)
2
21
3
1
Order By: Relevance
“…Interestingly, the AUC of the surrogate measures differed by sex. This result is consistent with those of a previous study [ 17 , 19 ]. Considering that estrogens promote peripheral fat storage, whereas androgens promote the accumulation of visceral abdominal fat, the alteration of sex hormone might affect the insulin resistance and the diagnostic performance of each measure for type 2 DM [ 37 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Interestingly, the AUC of the surrogate measures differed by sex. This result is consistent with those of a previous study [ 17 , 19 ]. Considering that estrogens promote peripheral fat storage, whereas androgens promote the accumulation of visceral abdominal fat, the alteration of sex hormone might affect the insulin resistance and the diagnostic performance of each measure for type 2 DM [ 37 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, the AUC value was much lower than those in previous studies. According to studies conducted in Iran, China, and Korea, the AUC value of HOMA-IR was approximately 0.7–0.8 [ 17 19 ]. Interestingly, a significant decline of the diagnostic performance of HOMA-IR for type 2 DM was observed with aging [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found an L-shaped association between HOMA-IR and annual changes in FEV1 and FVC using the multivariate GAM plot, and the suggested threshold of HOMA-IR for lung function decline was 2.4. As a surrogate marker of insulin resistance, several studies have shown that the cutoff value of HOMA-IR for the risk of developing type 2 diabetes mellitus and metabolic syndrome in the Korean population is approximately 2.5 [22][23][24]. Our ndings, consistent with those of previous studies, indicated that a decline in lung function may be metabolic complication due to the systemic effects of insulin resistance.…”
Section: Discussionsupporting
confidence: 90%
“…While NAFLD is an independent risk factor for cardiovascular complications [19], when combined with type 2 diabetes, it further increases the risk of systemic atherosclerosis [3]. Insulin resistance, a characteristic feature of both type 2 diabetes and NAFLD, is known as the key pathophysiology linking type 2 diabetes, NAFLD, and atherosclerosis [2,20]. However, little is known about the longitudinal effects of NAFLD or NASH on systemic atherosclerosis in type 2 diabetes.…”
mentioning
confidence: 99%